PENINGKATAN LITERASI DAN ADOPSI KEUANGAN DIGITAL BERBASIS QRIS MELALUI ANALISIS PELUANG DAN TANTANGAN PADA UMKM KERUPUK MARTABAK DESA KASEMEN KOTA SERANG - Suci Mutiara Sani; Risma Ridianti; Siti Hukmiatunnisa; Ruth Melani Putri Pesta; Yane Rohayatunnisa; Mila Nurmila (Yayasan Education and Social Center, 2026)
The low level of digital financial literacy among owners of the Kerupuk Martabak business in Kampung Bobojong, Serang City, most of whom have not adopted non-cash transactions despite owning smartphones, served as the starting point for this community service activity. The activity aimed to improve insight, explore opportunities, and map the challenges of QRIS adoption from the perspective of MSME financial management. The implementation method used a learning by doing approach through the stages of preparation, education, demonstration, and simulation, with a descriptive evaluation involving 18 participants consisting of business owners and local residents interested in starting their own businesses. The results showed an improvement in the partners' digital financial literacy in three aspects: the use of QRIS to monitor cash flow, awareness of separating business finances, and mitigation of digital transaction security risks such as fake QRIS schemes. This activity also identified three main challenges in the field, namely technical, cognitive, and regulatory constraints. The limitation of this activity lies in the evaluation which remained descriptive without pre-test and post-test. Nevertheless, the training succeeded in fostering the partners' initial awareness while also producing a recommendation on the need to integrate financial literacy programs with capital assistance through KUR, business legality (halal certification and BPOM), and comprehensive digital marketing.